"Analyse des performancesdes systèmes de communications optiques multiplexés employant des micro-résonateurs en anneau cascadés" - عبد الرزاق, سعود; عبد الرزاق, قادي; محمد, رضواني (Université d'El Oued, 2021)
"The evolution of data transmission by optical fiber has accelerated since the appearance of the wavelength division multiplexing (WDM) technique, which makes it possible to achieve bit rates of a few Tbit / s transported on a single and single fiber. Like any communications system, a fiber optic link consists of a transmitter, a fiber (channel) and a receiver. The optimization of the transmission quality is achieved through a good choice of components in each part of the link. In this context, we are interested in the study and analysis of the performance of multiplexed optical communications systems. This project focuses in particular on the performance analysis of multiplexed optical communications systems employing cascaded ring microresonators." "تسارع تطور نقل البيانات بواسطة الألياف الضوئية منذ ظهور تقنية تعدد الإرسال بتقسيم الطول الموجي (WDM)، مما يجعل من الممكن تحقيق معدلات بتات قليلة من s / Tbit تُنقل على ليف واحد ومفرد. مثل أ نظام اتصالات ، يتكون ارتباط الألياف الضوئية من جهاز إرسال وليف )قناة( وجهاز استقبال. يتم تحقيق تحسين جودة الإرسال من خلال اختيار جيد للمكونات في كل جزء من الارتباط. في هذا السياق ، نحن مهتمون بدراسة وتحليل أداء أنظمة الاتصالات الضوئية متعددة الإرسال. يركز هذا المشروع بشكل خاص على تحليل أداء أنظمة الاتصالات الضوئية متعددة الإرسال التي تستخدم رنانات دقيقة متتالية"
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: "Optical communication systems, multiplexing technique, micro-resonator, optical fiber."; أنظمة الاتصالات البصرية ، تقنية تعدد الإرسال ، الرنان الصغير ، ليف بصري